Development of consistent forms for the Gibbs equation and the entropy balance - Sliepcevich, C. M. (Rev. Téc. Fac. Ing. Univ. Zulia)
The principles of conservation of matter and energy are readily quantified in the mass and energy balances of the First Low of Thermodynamics. On the other hand formulation of a comparable balance equation for the Second Law tends to be more abstruse in traditional expositions. The objective herein is to demonstrate the basic Second Law equations–the Gibbs (or combined law) equation and the generalized entropy balance-can be obtained as a simultaneous result of combining the First Law mass and energy balances with corresponding energy transport of degradation functions. In this manner. consistency or reciprocity between the Gibbs equation and the entropy balance is assured. Another dividend from this approach is that it facilitates a more pragmatic interpretation of these relations.